The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/admsci11030097
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Higher Education Institutions to the SDGs—An Evaluation of Sustainability Reporting Practices

Abstract: The introduction of Agenda 2030 has impacted the public and private sectors. Agenda 2030 is a document that aims to promote collaboration and partnership between countries and the population for the achievement of 17 SDGs, which cover all the three dimensions of sustainability: environmental, social, and economic. Within the public organizations, higher education institutions (HEIs) have shown certain attention on the topic. In particular, for many HEIs, the publication of sustainability reports has represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 58 publications
2
45
1
1
Order By: Relevance
“…the Talloires Declaration, the Halifax Declaration, the SDG Accord and the Abuja Declaration) designed to foster sustainable development (SD) and education for sustainable development has increased over time (Lozano et al, 2015). Linked to the sustainability actions, the publication of reports is another instrument for institutions to disclose and publicise their commitment to sustainability and, by extension, the SDGs (Caputo et al, 2021). However, universities have been slow to adopt sustainability practices IJSHE 23,8 (Lozano, 2006;Velazquez et al, 2006) due to a resistance to change and a lack of awareness, interest and funding.…”
Section: Introductionmentioning
confidence: 99%
“…the Talloires Declaration, the Halifax Declaration, the SDG Accord and the Abuja Declaration) designed to foster sustainable development (SD) and education for sustainable development has increased over time (Lozano et al, 2015). Linked to the sustainability actions, the publication of reports is another instrument for institutions to disclose and publicise their commitment to sustainability and, by extension, the SDGs (Caputo et al, 2021). However, universities have been slow to adopt sustainability practices IJSHE 23,8 (Lozano, 2006;Velazquez et al, 2006) due to a resistance to change and a lack of awareness, interest and funding.…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by the Principles for Responsible Management Education (PRME), HEIs can influence students with responsible and sustainable business practices (Parkes et al 2017). The coexistence of different themes directly or indirectly related to the CSR paradigm underlined HEIs' social role (Caputo et al 2021; Rete delle Università per lo Sviluppo Sostenibile 2021). Contributing to the multidimensional goals identified by policymakers requires a holistic approach to evaluate the real contribution provided by companies to society (Cottafava et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability Evaluation: After measuring the extent to which the objectives have been achieved from the use of information and communication technology in the learning room, then the madrasah determines whether the program using this information and communication technology will be continued or discontinued or replaced with other programs (Caputo et al, 2021). The evaluation analysis of the sustainability of this program concluded that given the importance of information and communication technology to be used in learning spaces, this program continued with several notes that must be improved.…”
Section: Product Evaluation the Use Of Information And Communication ...mentioning
confidence: 99%